PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENERIMAAN TUNGGAKAN PAJAK BADAN PADA KPP PRATAMA PALEMBANG SEBERANG ULU - Aidil Fitrisyah; Ermadiani Ermadiani (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2014)
Tax is a very large source of state revenue and is used for the State Budget. Increasing tax revenues which are increasing year by year are also accompanied by greater tax arrears. One of the factors of the tax arrears is due to the level of awareness and taxpayer compliance (WP). This study aims to find out how much influence tax collection has with the Letter of Reprimand and Forced Letter on the Receipt of Corporate Tax Arrears at Palembang Seberang Ulu Primary Tax Office. The method used in this study is a quantitative method with emphasis on testing theory through measuring research variables with numbers and analyzing data empirically. In this study, researchers used primary data, namely data regarding the number of letters of reprimand and the number of sheets of forced letters issued to corporate taxpayers. While secondary data are data on the receipt of corporate tax arrears, agency history, and organizational structure. The population in this study is a corporate taxpayer registered at Palembang Seberang Ulu Primary Tax Office, which has tax arrears in 2010, 2011, and 2012. Based on the results of the research and discussion in this study regarding the effect of the number of reprimand letters and forced letters issued to the receipt tax arrears partially / individually, it can be concluded that both the number of letters of reprimand and the number of forced letters issued for corporate taxpayers have no significant effect on the receipt of corporate tax arrears at Palembang Seberang Ulu Primary Tax Office. The results of the study indicate that 12.9% of the receipt of agency tax arrears is explained by a reprimand issued while the side is 87.1% explained by other factors. This study also shows that 5% of the agency's tax arrears receipts are explained by forced letters issued while the 95% side is explained by other factors.